IDENTIFIKASI GEJALA PASCA VAKSINASI COVID-19 DOSIS KE-3 (BOOSTER) - Retno Sumara (Jurnal Keperawatan Muhammadiyah, 2023)
Objective:. COVID-19 is a type of disease that infects the human respiratory tract. Transmission of the COVID-19 virus is fast and aggressive. Vaccination is one of the preventive measures that is of concern to inhibit the spread of Covid-19. Booster doses of vaccination are carried out to maintain the effectiveness of the vaccine. AEFI is any medical event that is not expected to occur after immunization where the events are varied, because everyone experiences different symptoms. .Methods: The research design used a quantitative descriptive study with a population of 211 students and a sample of 138 using a purposive sampling technique. Data analysis using descriptive analytic.Results: The results showed that the AEFI symptoms that often appeared after the AstraZeneca, Moderna, Pfizer, and Sinovac booster doses of vaccination were Headache, Fever, Pain accompanied by weakness at the injection site, Muscle aches, Swelling at the injection site, Lethargy, Weakness/numbness throughout the body, Weakness on the muscles of the arms and legs, Cough/runny nose, other symptoms (local rash (swelling/red/itchy) on: skin, lips and eyes).Conclusion: KIPI is an effect caused after vaccination. By knowing these symptoms, it is hoped that the community can prevent and prepare for appropriate management in dealing with KIPI.